2011
DOI: 10.5380/rf.v41i3.24057
|View full text |Cite
|
Sign up to set email alerts
|

UTILIZAÇÃO DA SERRAGEM DE Eucalyptus spp. PARA A PRODUÇÃO DE TIJOLO MACIÇO CERÂMICO

Abstract: Objetivou-se neste trabalho verificar a viabilidade do processo de incorporação de serragem de Eucalyptus spp. para a confecção de produtos cerâmicos; avaliar em ensaios preliminares de laboratório o comportamento da argila e dos tratamentos constituídos com traços de mistura argila/serragem; avaliar a composição química da serragem e proceder a uma análise mineralógica da argila pelo teste de difração de raios X. Utilizaram-se 10 tratamentos com a mistura argila/serragem: 1:0 (testemunha), 2:1, 3:1, 4:1, 5:1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Other studies have considered 100% natural WW as a raw material for the production of MDP [6,25]. In addition, Mori et al [26] found that adding up to 11% WW was feasible without altering the technical properties of solid ceramic bricks.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have considered 100% natural WW as a raw material for the production of MDP [6,25]. In addition, Mori et al [26] found that adding up to 11% WW was feasible without altering the technical properties of solid ceramic bricks.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this way, the virgin resources are replaced by 20% in the panels and 11% in the ceramic brick on a mass basis (w/w). These percentages were defined according to technical research on the products [23,24,26]. Figure 2 shows the five scenarios evaluated for the disposal of WW.…”
Section: Scenarios Evaluatedmentioning
confidence: 99%
“…The main downsides of the produced mixtures are a higher porosity of the material and increased water absorbency [7][8][9] . To reduce the level of water absorption of products rich in silicon and aluminum oxide, alkali activators can be used.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos realizados por Dutra e Pontes (2002), que incorporaram serragem de madeira (0% a 30% em peso) nas massas cerâmicas para a produção de agregados leves de argila calcinada e obtiveram agregados com massa específica variando de 1,92 g/cm³ a 1,20 g/cm³, para temperatura de queima de 1.100 °C. Já estudos realizados por Mori et al (2011), que também incorporaram serragem de madeira para a produção de materiais leves de cerâmica vermelha, obtiveram resultados de massa específica dos testemunhos variando de 1,6 g/cm³ a 1,4 g/cm³, para testemunhos com incorporação de 10% e 33% em volume de serragem nas massas cerâmicas, queimadas a 950 °C. Rossignolo et al (2014) também estudaram a incorporação de serragem de madeira nas massas cerâmicas para a produção de agregados leves para concreto.…”
Section: Principais Características Dos Agregados Leves A)unclassified